KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING ATAS PENGARUH CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Eki Andhika Ratnawardhani (Universitas Negeri Malang, 2017)
This research aims to test and search for empirical evidences of: (1) the impact of corporate governance toward firm value. (2) the impact of corporate governance toward dividend policy. (3) the impact of dividend policy toward firm value. (4) the impact of corporate governance toward firm value through dividend policy. The sample consist of 44 corporates listed in Indonesia Stock Market who are participating in the survey conducted by The Institute Indonesian of Corporate Governance on 2011 – 2015 and distribute of dividends. Analysis method used in this study is path analysis to test both direct and indirect impact. The result of this study shows that there is no significant impact of corporate governance toward the corporate value. Corporate governance has positive impact toward dividend policy which is consistent with the hypothesis. Dividend policy has positive impact toward corporate value. Dividend policy would mediate the impact of corporate governance toward corporate value.